Interface engineered surface morphology evolution of Au@Pd core–shell nanorods. Issue 45 (8th November 2018) - Xu, Yanchao; Cui, Xiaoqiang; Qi, Kun; Wei, Shuting; Wang, Qiyu; Zheng, Weitao
Abstract : The surface morphology evolution of Au@Pd core–shell nanorods was controlled by adjusting the solution supersaturation. Abstract : Engineering the interfacial structure of bimetallic nanocrystals is an effective method to improve their electrocatalytic performances. Here, we design a facile strategy for controlling the surface morphology evolution of Au@Pd core–shell nanorods by adjusting the solution supersaturation. The Pd shell of the as-prepared Au@Pd bimetallic nanorods can be modulated from a (111) facet-exposed island to a (100) facet-exposed conformal shell. The conformal shell structure exhibited enhanced catalytic performance toward the ethanol oxidation reaction, while the core-island structure possessed better catalytic stability. This work provides a facile method for interfacial engineering of bimetallic nanocrystals with desired morphology and properties.